2012
DOI: 10.1021/jp211282z
|View full text |Cite
|
Sign up to set email alerts
|

Self-Diffusion of Ions in Nafion-117 Membrane Having Mixed Ionic Composition

Abstract: The self-diffusion coefficients (SDCs) of Na(+), Cs(+), and Ba(2+) have been determined in Nafion-117 membrane having mixed cationic compositions. Membranes with different proportions of Na(+)-Cs(+), Cs(+)-Ba(2+), Na(+)-Ba(2+), and Ag(+)-Ba(2+) cations have been prepared by equilibrating with solutions containing different ratios of these cations. The SDCs of the cations (D(Na), D(Cs), D(Ba)) and the ionic compositions of the membrane have been determined using a radiotracer method. For the Na-Cs and Cs-Ba sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
45
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(46 citation statements)
references
References 25 publications
1
45
0
Order By: Relevance
“…A consequence of this phenomenon is that Nafion-H + and Nafion-Cs + have the similar d dry at 10% RH, although the former membrane accommodates 3 more water molecules per SO 3 sites (including the residual water). The unique properties of Nafion-Cs + owing to its very low charge density and strong interaction with sulfonate (SO 3 -) sites was discussed previously, and Cs + was suggested to be transferred through the interfacial regions, not the ionic domains [26,29].…”
Section: Small-and Wide-angle X-ray Scattering (Saxs/waxs)mentioning
confidence: 85%
See 1 more Smart Citation
“…A consequence of this phenomenon is that Nafion-H + and Nafion-Cs + have the similar d dry at 10% RH, although the former membrane accommodates 3 more water molecules per SO 3 sites (including the residual water). The unique properties of Nafion-Cs + owing to its very low charge density and strong interaction with sulfonate (SO 3 -) sites was discussed previously, and Cs + was suggested to be transferred through the interfacial regions, not the ionic domains [26,29].…”
Section: Small-and Wide-angle X-ray Scattering (Saxs/waxs)mentioning
confidence: 85%
“…Overall, cations have been demonstrated to influence a PFSA membrane's conductivity, selfdiffusion, water-uptake capacity in liquid water, transference number, permeability, and selectivity [16][17][18][19][20][21][22][23][24][25][26][27][28][29]. In addition, most of these properties have been shown to be interrelated as most of them are influenced by the cation's hydration energy and interaction between the ionic moieties and water molecules.…”
Section: Introductionmentioning
confidence: 99%
“…2, 12-15, 17, 19-23 Investigations on PFSAs in proton and other cation forms have provided insight into the ion transport mechanisms, such as water-mediated ion transport and role of hydrogen bonding. 4,10,15,17,19,21,[24][25][26][27] Impact of a cations associated with not only its interaction strength and mobility within the ionic region, but also the intermediate region occupied by the fluoroether side-chains, which affect the polymer-chain segmental motion and morphology. 2,10,19,23,28 To elucidate how these interactions influence ionomer behavior, many studies focused on measuring the properties of PFSA membranes exchanged with different cationic forms.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16] Most of these studies focus on the effect of cations, but a few reports on anion dependence on transport of cations are also available. 17,18 Goswami and co-workers, for example, have shown that mercury(II) ions in solution are absorbed in different oxidation states, depending on the electrolyte present in the solution from which they are taken up by Nafion. When loaded from Hg(NO 3 ) 2 , the charge of the species inside the membrane has been found to be +2, as expected.…”
Section: Introductionmentioning
confidence: 99%